Negotiating Islamic Unity In A Fragmented World: A Comparative Study Of Ummatan Wahidah In Modern Sunni And Shii Exegesis - Moh. Azwar Hairul; Mustaqimah; Ahmed Abdul Malik; Basri (Faculty of Ushuluddin and Religious Studies, State Islamic University (UIN), 2026)
Non-Indexed Publication